EFEKTIVITAS PEMBELAJARAN KOMPUTER AKUNTANSI DI LABORATORIUM KOMPUTER AKUNTANSI SMK NEGERI 3 PALEMBANG - Hendra Wijaya; Ikbal Barlian; Siti Fatimah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2014)
This research entitled The Effectiveness of Computer Accounting Learning at Computer Accounting Laboratory SMK Negeri 3 Palembang. Problems in this research is how the effectiveness level of computer accounting learning in computer laboratory accounting SMK Negeri 3 Palembang seen from the aspect of teacher activity in learning, learners activity in learning, and learners learn result. The study population is all students of class XII competency of accounting expertise at SMK Negeri 3 Palembang which amounted to 139. Sampling is done through cluster random sampling, and the sample of research is class XII Ak.1 of 48 students. Data collection techniques used observation and documentation. In analyzing the data used the average formula. From the results of data analysis, it is known that computer accounting learning in computer laboratory accounting SMK Negeri 3 Palembang seen from the aspects of teacher activity in learning, learners activities in learning, and learning outcomes of students has been effective. This is seen from the observation of teacher activity, computer accounting learning in accounting computer laboratory including very effective category with the average percentage of 83.33%. Student activity is effective with average percentage of 77.77%, and learning outcomes of learners have achieved complete learning individually and in classical with the average value of learners that is 88.75. Thus the success rate of computer learning accounting in computer laboratory accounting SMK Negeri 3 Palembang is effective. Therefore, the implementation of computer accounting learning in this computer accounting laboratory can be continued for the learning process.